Summer weather conditions and tourism flows in urban and rural destinations - Martin Falk (European Regional Science Association (ERSA), 2014)
The relationship between weather and tourism demand has been widely investigated for different locations and for different seasons. Although weather and climate conditions are widely seen as an important factor for tourism, relative little is known about their effects over a longer time period. Given that about 50% of tourists come to Austria during summer months May to September, favourable summer weather can play a very important role in determining the number of visitor nights and arrivals. The relationship between weather and tourism is particularly important for regions with moderate climate conditions. It is expected that summer tourism in these location will benefit from global warming (Nicholls and Amelung 2008). The aim of the paper is to investigate the impact of weather on visitor nights using regional data for Austria at the level of provinces for the period 1974-2012. In particular, we distinguish between the capital region Vienna and eight other provinces. The econometric model is based on the seemingly unrelated regression method which makes it possible to account for the cross-regional correlations. We also allow for lagged effects of weather. We provide separate estimates of the relationship between visitor nights and weather for each province. Global warming has lead to new interest in the weather-tourism relationship. More and more is being published on the relationship between weather patterns and tourism demand (see Becken, 2013; Gössling et al., 2012; Kaján & Saarinen, 2013 for surveys). A general finding of the literature is that there is a significant relationship between domestic tourism demand and weather conditions, while foreign (inbound and outbound) tourism is only affected by weather conditions with a 1-year (or -season) lag. Few studies have investigated the impact of summer weather on tourism demand in regions with cooler climate conditions and moderate temperatures, which are likely to gain from climate change (Serquet & Rebetez, 2011 is an exception). Austria is an interesting country case to study with a long tradition in summer alpine tourism. However, summer tourism in the Alps has suffered from a steady decline starting from the 1970s and has now stabilized. Results using the seemingly unrelated regression model show that sunshine duration and temperatures have a significant and positive impact on both domestic and German tourism demand for most of the provinces. However, sunshine and temperatures affect German overnight stays only with a one year lag. Weather effects are larger in August and September than in June and July. Overall, the impact of weather is highest in Salzburg and Upper Austria where current and lagged sunshine or temperature can explain between 25 and 50 percent of the variation of overnight stays. In contrast, weather conditions are not relevant for visitor nights in Vienna.
Keywords: R11; L83; 330; tourism demand; weather factors; seemingly unrelated regression modelm; regions